Spatiotemporal Variability of the Southern Annular Mode and its Influence on Antarctic Surface Temperatures - Wachter, Paul; Beck, Christoph; Philipp, Andreas; Höppner, Kathrin; Jacobeit, Jucundus; 2 Institute of Geography Augsburg University Augsburg Germany; 3 Institute Development‐Space Research and Technology (VO‐IR) German Aerospace Center (DLR) Köln Germany (Journal of Geophysical Research: Atmospheres, 2020)
The Southern Annular Mode (SAM) is the predominant atmospheric variability mode in the Southern Hemisphere. In this paper, we present the spatial variability results of the SAM pattern for the period 1979–2018. The SAM‐intrinsic pattern variability analysis is based on the principal component analysis (PCA), which is carried out for the ERA‐Interim 500 hPa geopotential height (GPH) data set. A spatiotemporally resolved data set of SAM pattern maps (PCA loadings) is derived by projecting monthly shifted sub‐sequences of SAM index values (PCA scores) on the corresponding GPH anomalies. The dominant SAM structure within single pattern fields is mapped automatically and can be interpreted as the Southern Hemisphere polar front. This data set allows an analysis of the geographical positions of the characteristic circumpolar SAM structure over four decades and shows considerable variability over space and time. Five different states of SAM patterns, which are associated with characteristic circulation anomalies during different phases of the study period, are identified. Station‐based Antarctic temperature anomalies can be synoptically explained by these circulation anomalies. The overall latitudinal trend of the SAM pattern indicates an intensification of the meridional structure, especially over the East Antarctic Southern Ocean. Furthermore, we show that the SAM pattern variability is significantly correlated with the Pacific Decadal Oscillation and the Atlantic Multidecadal Oscillation. Composites of 500 hPa GPH anomalies during the positive and negative phases of the respective indices indicate teleconnections with Pacific Decadal Oscillation and Atlantic Multidecadal Oscillation, and this can explain latitudinal trends of the SAM pattern. Key Points: We present a new approach to examine the spatiotemporal Southern Annular Mode pattern variability. Station‐based Antarctic temperature anomalies are related to different structures of the Southern Annular Mode. The trend pattern shows an increasing meridional ...